Court of Justice of the European Union as an institutional actor : judicial lawmaking and its limits - Horsley, Thomas, 1984- (Cambridge, United Kingdom : Cambridge University Press, 2018)
The EU Treaties bind the Court of Justice of the European Union as an institution of the Union. But what does that mean for judicial lawmaking within the EU legal order? And how might any limits set out in the EU Treaties be effectively applied to the Court of Justice as lawmaker? This book interrogates these fundamental and underexplored questions at a critical juncture in European integration. It argues that the EU Treaties should be considered to function as the principal touchstones for assessing the internal constitutionality, and hence legitimacy, of all Union institutional activity - including the work of the Court. It then examines how far the Court of Justice complies with the EU Treaty framework in the exercise of its interpretative functions. The results of that analysis are striking and offer scholars powerful new insights into the nature and limits of the Court's role within the EU legal order. --
The EU Treaty framework as constitutional touchstone -- The EU Treaty framework and the constitutional context of European integration -- The Court of Justice , the Treaty framework and Constitutional Issue No. 1 -- The Court of Justice , the Treaty framework and Constitutional Issue No. 2 -- The Court of Justice , the Treaty framework and Constitutional Issue No. 3 -- The feedback loop : The Court of Justice and its interlocutors -- Conclusion : three contemporary problems, four reform proposals.
Includes bibliographical references and index.
Keywords: Court of Justice of the European Union; Court of Justice of the European Union; European Union; Court of Justice of the European Union; European integration; European constitutional law; Judicial activism